Human security in a globalised world: the case of Gaza - Hossain, Ishtiaq; Adams, Isiaka Abiodun (IAIS and Cordoba Foundation, 2014)
This chapter is divided into three parts. Part One deals with the fundamentals of human security, and puts forth the argument that the concept of human security is a universal one. It should not be viewed merely as a Western-inspired concept. Next, the Islamic perspective of human security is explored in detail by drawing on the Qur’an and Hadith, historical narratives as well as contemporary praxis. The third section deals with the ‘matters’ and requirements of human security issues through analysis of the sources of human insecurity in Gaza. The chapter concludes with recommendations on how to deal with the human security challenges in Gaza.